Bioassay assessment of metarhizium anisopliae (metchnikoff) sorokin (deuteromycota: hyphomycetes) against Oncometopia facialis (signoret) (hemiptera: cicadellidae) - Pria Júnior, Wolney Dalla (Sociedade Brasileira de Microbiologia, 2008)
Citrus Variegated Chlorosis (CVC) is an economically important, destructive disease in Brazil and is caused by Xylella fastidiosa and transmitted by sharpshooter insects. In this study, the efficacy of the fungus Metarhizium anisopliae in controlling the sharpshooter Oncometopia facialis was studied by bioassay conditions. In the bioassay, insects were sprayed with a suspension containing 5 X 10(7) conidia mL(-1). Adults captured in the field were treated in groups of 10 in a total of 11 replications per treatment. Significant differences between the natural mortality and the mortality of insects treated with the fungus were observed 6 days after inoculations (P<0.05). These significant differences increased until 10 days after treatment. The fungus caused 87.1% mortality, with the LT50 varying from 5 to 6 days. The LC50 was 1.2 X 10(6) conidia mL(-1), varying from 7.7 X 10(5) to 2 X 10(6) conidia mL(-1). The results showed that the sharpshooter O. facialis was susceptible to the entomopathogenic action of M. anisopliae in controlled condition during bioassay.